2021
DOI: 10.1111/jocn.15659
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a psycho‐educational intervention to improve pain management after day surgery: A randomised clinical trial

Abstract: Aims and objectives To evaluate the effectiveness of a psycho‐educational intervention for shoulder and breast day surgery patients in decreasing pain intensity and pain interference with function and strengthening adherence with the analgesic regimen; and further to identify factors that influence average pain intensity and pain interference with function. Background Pain is one of the most prevalent symptoms after day surgery. However, pain management is left to the patients and family, and interventions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
(48 reference statements)
2
4
1
Order By: Relevance
“…In contrast, Susini et al 6 recently reported 40.6% postdischarge pain of NRS 4 or higher after ambulatory BC surgical procedures comparable to ours, but with a less extensive pain prophylaxis. In our study, younger patients had significantly 2–5 times higher odds for postdischarge pain than older patients, which is similar to prior studies 20,22–25 …”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In contrast, Susini et al 6 recently reported 40.6% postdischarge pain of NRS 4 or higher after ambulatory BC surgical procedures comparable to ours, but with a less extensive pain prophylaxis. In our study, younger patients had significantly 2–5 times higher odds for postdischarge pain than older patients, which is similar to prior studies 20,22–25 …”
Section: Discussionsupporting
confidence: 92%
“…In our study, younger patients had significantly 2-5 times higher odds for postdischarge pain than older patients, which is similar to prior studies. 20,[22][23][24][25] We found no association between pain and surgical procedure, which is in contrast to the study by Rehberg et al 24 Our result may be related to the overall low surgical invasiveness in our day-surgical study population. At OUH, all patients with planned mastectomy are offered an immediate reconstructive procedure, unless contraindicated, and subsequently transferred to inpatient care.…”
Section: Postdischarge Paincontrasting
confidence: 99%
See 3 more Smart Citations